DETECTING THE AFFECTED AREAS OF MOUNT SINABUNG ERUPTION USING LANDSAT 8 IMAGERIES BASED ON REFLECTANCE CHANGE - . Suwarsono; . Hidayat; Jalu Tejo Nugroho; . Wiweka; . Parwati; M. Rokhis Khomarudin (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2015)
The position of Indonesia as part of a